Creating the city: An interview with Antonia Darder and Pepón Osorio. (September 2017) - Herman, David; Kraehe, Amelia; Bartholomee, Lucy; Lewis, Tyson
Today there is a lot of discussion about creative economies and how cities are the engines driving growth in a variety of industries. But cities are not merely rows of buildings, or sets of laws, such as zoning ordinances or parking regulations. A city is, rather, a set of dynamic experiences that we all participate in as co(labor)ators. As a way to explore issues of urban spaces and art, the authors organized a public dialogue on issues pertaining to arts, community, identity, education, and policy with two leading artists/educators/activists: Pepón Osorio and Antonia Darder. The interview is wide ranging and brings into focus voices and perspectives often left out of policy debates concerning the politics of art, art education, and activism in urban environments. The authors of this article then propose four core principles drawn from the dialogue that can guide policy reforms for the arts in urban schools. Such principles argue that policy must be made from within the creative commonwealth of cities rather than above or outside it.